Penerapan Metode Talaqqi dalam Pendahuluan Pembelajaran untuk membentuk bacaan Al-Qur’an siswa kelas X SMK Islam Al-Hikmah Mayong Jepara - Nikmah, Wakhidatun; Marwan, Iwan; Anam, Masrul (LPTK UIN Syekh Wasil Kediri, 2022)
This study aims to determine the application of the Talaqqi method and how much influence it has on memorizing prayer readings for class X Islamic SMK Al-Hikmah Mayong Jepara. This research is a qualitative research in the form of classroom action research which is one of the efforts to improve the quality of learning and teacher professionalism. Place The author's research was conducted at Al-Hikmah Mayong Islamic Vocational School Jepara from August 2021 to June 2022. The research subjects were 37 students of class X TKR 1 Islamic Vocational High School Al-Hikmah Mayong Jepara 21 for the 2021/2022 academic year. Data were collected by means of observation, interviews, and documentation. The results of the research that the author did it can be concluded that the learning carried out before the act of reading the prayer readings is still relatively low, by using the talaqqi method, learning to read the prayer readings has increased gradually with the first cycle to the second cycle which indicates that the talaqqi method is able to improve memorization and student reading.